Restoration of Sitting Balance and Bladder Control via Epidural Stimulation in SCI: A Clinical Study - Kaura, Surbhi; Zafar, Shahiduz; Majumdar, Pritam (Journal of Neonatal Surgery, 2025)
Background: Spinal cord injury (SCI) often results in impaired mobility and bladder dysfunction, significantly reducing an individual's quality of life. Epidural spinal cord stimulation (ESCS) has shown potential in enhancing functional outcomes in individuals with SCI by modulating spinal neural circuits. Methodology: This study investigated the effects of ESCS on walking ability, sitting balance, and bladder function in individuals with thoracic SCI. Ten (10) participants with lesions ranging from T6 to T10 underwent an 8-week intervention. Functional assessments were conducted pre- and post-intervention using the Timed Up and Go (TUG) test, the Function in Sitting Test (FIST), and the Neurogenic Bladder Symptom Score (NBSS). We performed Paired t-tests to analyze the significance of changes across the measured variables. Results: Statistical analysis demonstrated significant improvements in all three outcome measures. The average TUG time decreased by 385.4 seconds (p < 0.0001), indicating improved mobility. FIST scores showed improvement by an average of 31.9 points (p < 0.0001), reflecting enhanced sitting balance. NBSS scores decreased by 13.4 points (p < 0.0001), suggesting improved bladder function. The effect sizes were large across all measures, supporting the clinical relevance of the findings. Conclusion: ESCS appears to be a promising therapeutic approach for enhancing mobility, postural control, and bladder function in individuals with thoracic SCI. These findings support the integration of ESCS into rehabilitation protocols to enhance quality of life in this population.